The Role of Work Family Conflict, Work Stress and Burnout in Improving Employee Performance during the Covid-19 Pandemic: Peran Work Family Conflict, Stres Kerja dan Burnout dalam Meningkatkan Kinerja Karyawan pada Masa Pandemi Covid–19 - Annajiyah, Ainun; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the Effect of Work Family Conflict, Work Stress, and Burnout on employee performance at CV. Ko Pi Mana during the Covid-19 pandemic. This research is a descriptive study using quantitative methods. Sampling in this study was carried out with the Non Probability Sampling technique with the Purposive Sampling method and the number of samples in this study were 96 respondents. Data collection techniques using a questionnaire. The data analysis technique used in this study was multiple linear regression using the SPSS version 26 program.The results of this study prove that Work Family Conflict has no affect on employee performance during the Covid-19 pandemic, work stress affects employee performance during the Covid-19 pandemic, and Burnout affects employee performance during the Covid-19 pandemic.